A doubly bridged bis(phenylethynyl)benzene: different from a twisted tolan - Hodecker, Manuel; Kozhemyakin, Yury; Weigold, Svenja; Rominger, Frank; Freudenberg, Jan; Dreuw, Andreas; Bunz, Uwe H. F. (Chemistry - a European journal, 2020)
The synthesis of a doubly bridged 1,4-bis(phenylethynyl)benzene is reported. The target displays photophysical properties, distinctly different from that of its congeners, the singly bridged tolans. Quantum-chemical calculations suggest a lack of planarization of the bridged bis(phenylethynyl)benzene in the first excited state.